EKSEKUSI PUTUSAN PENGADILAN AGAMA KOTA YOGYAKARTA TENTANG MUT'AH PADA KASUS PERMOHONAN CERAI TALAK - Mahmud, Datuk (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
This paper tries to examine related to the fulfillment of mut'ah which is applied in the Religious court of Yogyakarta City namely to find out how the efforts and solutions given by the Judge regarding the fulfillment of mut'ah. in order to achieve the objectives of law enforcement in the form of justice, benefit and legal certainty. This research is a field research, namely examining in the religious court of Yogyakarta City. The nature of the research used is prescriptive. The approach used in this research is the sociology of law approach with the method used from satjipto Raharjo's theory of progressive law and maslahah mursalah theory. Based on the research, it was found that the efforts and solutions related to mut'ah were carried out by religious court of Yogyakarta city, namely by fulfilling the wife's rights in the form of mut'ah given before the divorce pledge, including the burden in the verdict and also giving advice so that the husband voluntarily fulfills the mut'ah and the judge plays an important role with his Ex officio.